(untitled) (International Journal of Engineering and Computer Science, 2018)
A communication system is provided that includes a transmitter device and a receiver device. The transmitter device transmits input data as a transmitted signal having the known non-linear distortion (NLD) characteristic. The receiver receives a received signal that represents a channel affected version of the transmitted signal and that has the known NLD characteristic. The received signal includes power amplifier distortion (PAD) induced by the transmitter device’s power amplifier. To reduce the NLD by reducing the PAPR of multicarrier system and PADs at transmitter side by using techniques and simulation in MATLAB